Stacked Dual‐Pore Architecture for Deciphering and Manipulating Dynamics of Individual Nanoparticles. Issue 11 (7th October 2020) - Liao, Caizhi; Antaw, Fiach; Wuethrich, Alain; Trau, Matt
Abstract: Understanding the behavior and interactions of nanoscale objects in selected microenvironments represents a great gateway to explore complex processes in nature. Label‐free methods such as resistive‐pulse sensing (RPS) have emerged as the most promising toolkits to decipher the characteristics of nano‐entities, nanoparticles in particular, with single molecular resolution. However, current single pore systems are inapplicable for sensing and controlling simultaneously single nanoparticles in motion. Here, two‐photon nanolithography to create vertically stacked RPS dual‐pores with precise 3D structure is proposed for the first time. The prepared dual‐pores afford time of flight analysis to finely decipher the molecular dynamics in terms of nanoparticle transport velocities and inter‐particle coupling effects. By further optimizing the 3D pore geometry, it is demonstrated that these dual‐pores can be applied for single nanoparticle capture and release studies. Abstract : Novel 3D miniaturized dual‐pore construct is prepared as a robust platform for resistive‐pulse sensing. The vertical dual‐pore system generated by two‐photon nanolithography affords to finely decipher the single molecular dynamics in terms of nanoparticle transport velocities and inter‐particle coupling effects, and is suited for single nanoparticle capture and release studies.